Effect of Heparin on the Activation of Factor XII and the Contact System in Plasma - Pixley, Robin A; Cassello, Anita; De La Cadena, Raul A; Kaufman, Nathan; Colman, Robert W (Thrombosis and Haemostasis, 1991)
We examined in purified systems and in human plasma whether heparin serves as a contact system activating compound. Purified human factor XII zymogen was not activated by heparin through an autoactivation mechanism, but was activated in the presence of purified prekallikrein. Zn2+ (12 εM) did not support autoactivation by heparin. The activation of factor XII and the contact system by heparin in plasma anticoagulated with citrate or with hirudin (not chelating ions) was examined by the cleavage of 125I-labeled factor XII and high molecular weight kininogen (HK). Heparin at 1.6 and 16 USP U/ml was not able to produce activation, in contrast to dextran sulfate (20 εg/ml) which supported activation of both factor XII and HK. This study indicates that heparinized plasma does not support activation of the contact system mediated through activation of factor XII. It is not expected that heparin anticoagulant therapy will contribute to activation of the contact system.